Mechanism of Multi-Organ Injury in Experimental COVID-19 and Its Inhibition by a Small Molecule Peptide - Paidas, Michael J.; Sampath, Natarajan; Schindler, Emma A.; Cosio, Daniela S.; Ndubizu, Chima Obianuju; Shamaladevi, Nagarajarao; Kwal, Jaclyn; Rodriguez, Suset; Ahmad, Anis; Kenyon, Norma Sue; Jayakumar, Arumugam R. (Frontiers in Pharmacology, 2022)
Severe disease from SARS-CoV-2 infection tend to be accompanied by multi-organ failure. The involvement of different organs in these patients results in increased mortality rate. However, underlying mechanisms of SARS-CoV-2-induced multi-organ failure and subsequent death are still largely unknown. Cytokine storm, increased levels of inflammatory mediators, endothelial dysfunction, coagulation abnormalities, and infiltration of inflammatory cells into the organs has been implicated in the pathogenesis of COVID-19. One potential consequence of immune/inflammatory events is the acute progression of generalized edema, which may lead to death. We therefore examined the involvement of water channels in the development of edema in multiple organs and their contribution to organ dysfunction in a Murine Hepatitis Virus-1 (MHV-1) mouse model of COVID-19. Using this model, we recently reported multi-organ pathological abnormalities, animal death similar to that reported in humans with SARS-CoV-2 infection. We now identified an alteration in protein levels of AQPs 1, 4, 5 and 8 and associated oxidative stress, along with various degrees of tissue edema in multiple organs, which correlate well with animal survival post-MHV-1 infection. Furthermore, our newly created drug (a 15 amino acid synthetic peptide, known as SPIKENET) that was designed to prevent binding of spike glycoproteins with their receptor(s), ameliorated animal death and reversed altered levels of AQPs and oxidative stress post-MHV-1 infection. Collectively, our findings suggest the possible involvement of altered aquaporins and the subsequent edema, likely mediated by virus-induced inflammatory and oxidative stress response, in the pathogenesis of COVID-19 and the potential of SPIKENET as a therapeutic option.